PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Tiana Octaviani; Syahrul Anwar, Yusuf Junaedi (ADISAM PUBLISHER, 2025)
This study aims to determine the effect of Team Ganes Tournament (TGT) learning model on students' mathematical communication skills, as well as to identify differences in mathematical communication skills between students taught usingTeam Ganes Tournament (TGT) learning model and students taught without usingTeam Ganes Tournament (TGT) learning model. This research was conducted at La Tansa 2 Junior High School. The research method used was true experimental with pretest-posttestcontrol group design. The research sample consisted of 30 students in the experimental class and 30 students in the control class selected using simple random sampling technique. The instrument used was a description test of 5 questions. The results of this analysis using simple linear regression showed a significance of 0.008, which means there is a significant effect. In addition, the result of t-test with Independent Sample T-Test shows a significance of 0.000, which is smaller than 0.05, so H₀ is rejected and H₁ is accepted. This indicates that there is a significant difference in mathematical communication skills between students taught using theTeam Ganes Tournament (TGT) learning model and students taught using conventional learning